Alteration of Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL) after treatment in the Helicobacter pylori-positive gastric ulcer: Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL) - Chu, Yunxiang; Jin, Lin; Weng, Yan; Liu, Xiaochuan (Journal of Medical Biochemistry, 2025)
0